The Influence of TikTok Live, Preloved Clothing Products, Promotions, and Discounts on Students’ Consumption Patterns - Apolonia Jafrisma; Maria Imakulata Pongge; Agnes Susanti Indrawati (Economics and Digital Business Review, 2026)
This study is motivated by the increasing use of TikTok Live as a digital shopping medium, particularly for purchasing preloved clothing among university students. This study aims to analyze the influence of TikTok Live, preloved clothing, and promotions and discounts on the consumption patterns of students at the Faculty of Economics and Business, Widya Mandira Catholic University Kupang. This research used a quantitative approach with 100 respondents as the sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that TikTok Live has a positive and significant effect on students’ consumption patterns, preloved clothing has a negative and significant effect, while promotions and discounts have a positive and significant effect. Simultaneously, the three variables significantly influence students’ consumption patterns, with an Adjusted R Square value of 0.883. This means that 88.3% of the variation in students’ consumption patterns can be explained by TikTok Live, preloved clothing, and promotions and discounts, while the remaining 11.7% is influenced by other factors outside the research model.